Empowerment through work: the cases of disabled individuals and low-skilled women workers on the US–Mexican border. Issue 3 (16th March 2019) - Castañeda, Ernesto; Chiappetta, Casey; Guerrero, Laura; Hernandez, Alma
Abstract: This article discusses workers at two organizations: one employing disabled individuals and another employing low-skilled Mexican-American women. Workers at both organizations show positive effects from employment, including having increased self-efficacy and self-esteem, valuing work as a source of income and personal growth, as well as developing a sense of community. These perceptions contrast sharply with statements presented about how they viewed themselves and their abilities before working in these organizations. Through comparisons between these two sets of experiences, we show how individuals draw meaning, dignity, self-esteem, and empowerment from work.